How growth mindset influences mathematics achievements: A study of Chinese middle school students - Dong, Lianchun; Jia, Xiaoying; Fei, Yaxin (Frontiers in Psychology, 2023)
It has been suggested that students with growth mindsets are more likely to achieve better mathematics learning results than their counterparts with fixed mindsets. However, inconsistent and some even contradictory results have been reported in recent studies which examined the associations between growth mindset and mathematics achievements, suggesting the complexity regrading the effects of growth mindset on academic achievements. This study aims to examine students’ growth mindsets, failure attributions, intrinsic motivation, mathematics self-efficacy, mathematics anxiety and mathematics achievements in one model to capture the sophisticated functioning processes of growth mindset. A total number of 266 middle school students in China participated in this study. Students’ mindset and related variables (i.e.,motivations to learn mathematics, attributions of failure in mathematics, mathematics anxiety, mathematics self-efficacy ) were measured at year 7, the first year of junior middle school in China. These students’ mathematics learning outcomes were tracked from year 7 to year 9, the end of junior middle school. Structural equation modelling (SEM) was used to investigate the relations among students’ growth mindsets, failure attributions, intrinsic motivation, mathematics self-efficacy, mathematics anxiety and mathematics achievements. The results show that: (1) growth mindset doesn’t directly predict mathematics achievements; (2) growth mindset indirectly influences mathematics achievements through intrinsic motivation; (3) failure attributions and mathematics self-efficacy sequentially mediate the association between growth mindset mathematics achievements; (4) failure attributions and mathematics anxiety sequentially mediate the relationship between growth mindset mathematics achievements. The results of this study contributes a better understanding about how growth mindsets make impacts on middle school students’ mathematics achievements.